Prosocial Behavior in Toddlerhood: The Contribution of Emotion Knowledge, Theory of Mind, and Language Ability - Brazzelli, Elisa; Pepe, Alessandro; Grazzani, Ilaria (Frontiers in Psychology, 2022)
While scholars have previously investigated the respective contributions of emotional knowledge and language ability to toddlers' prosociality, no studies to date have featured a battery of multiple direct measures assessing both of these abilities plus theory of mind on the one hand, and prosocial behavior on the other hand. In contrast, we conducted the present cross-sectional study with a view to evaluating the unique contributions of each of these three social cognition variables as antecedents of prosocial conduct during toddlerhood, measuring them via a series of individually administered standardized tasks. Furthermore, given that the existing literature documents mixed gender effects, we also set out to explore the role of gender in toddlers' prosociality. Finally, we also controlled for any effects of age on the patterns of association among the key variables. Participants were 127 children aged between 24 and 36 months (M = 29.2 months; SD = 3.5). We identified significant correlations among the variables under study. In addition, stepwise multiple regression analysis suggested that each of the social cognition (SC) abilities – i.e., emotion knowledge, theory of mind, and language - made a unique contribution to explaining variance in prosocial behaviors (PB). These findings show that SC is already associated with PB in toddlerhood and suggest the importance of fostering social cognition competence from the early years, with a view to increasing children's propensity to engage in prosocial conduct.